Policies based on demonstration effect could have suboptimal outcomes - Pradhan, Mamata; Roy, Devesh; Kishore, Avinash; Sonkar, Vinay Kumar (2017)
The debate in India regarding the delivery mechanism for the Public distribution System (PDS) has been polarised along the lines of cash versus kind transfer, inclusion criteria over exclusion criteria for beneficiary selection and the composition of product portfolio. This debate has been revitalised with the news that government is contemplating scrapping PDS, and replacing it with direct benefit transfer (DBT) for food because of encouraging results from pilots in Haryana and Puducherry. Though the PDS continues to be the fulcrum of food subsidisation, states like Bihar, Andhra Pradesh, Madhya Pradesh and Delhi, are conducting pilots for alternative mechanisms. Karnataka, recently made ration-card-holders eligible to buy rations at any PDS shop within the state i.e. not only their preassigned shops. Amid all these, one facet that deserves attention is: What do the beneficiaries of this system themselves want? Do they want a DBT, a food stamp, or the traditional PDS with some rough edges smoothed? Is the transferability of PDS across shops the preferred option or a purchasing power preserving DBT would make them happier? These questions relate to the rubric of demand assessment. Common sense might suggest that for maximum effectiveness, programmes like the PDS have an inbuilt system for such assessment. Yet, hardly any government programme ever carries out a demand assessment, and the PDS is no exception.